Ethnobotanical Survey of Plants Commonly used for Diabetes in Tarlac of Central Luzon Philippines - Mina, Erwin C.; Mina, Josefina F. (IIUM Medical Journal Malaysia, 2017)
Introduction: Plants have been used for the treatment of diabetes in Philippine system of medicine and in other countries. They provide clues for the development of new and better oral drugs for diabetes due to the fact that prevalence of diabetes is on a steady upsurge worldwide and identified as one of the leading causes of mortality in Philippines. Methods: An ethnobotanical survey was carried out in Tarlac of Central Luzon Philippines to evaluate the relative efficacy of the plants used to treat diabetes. A total number of 450 respondents medically diagnosed of having diabetes were interviewed using a previously prepared questionnaire. Fidelity levels (FLs) and use values (UVs) were calculated to identify and verify most preferred plant species used in study areas. Results: A total of 25 plant species are utilized by the respondents to treat diabetes. Medicinal plants commonly utilized are Momordica charantia Linn., Moringa oleifera Lam, Annona muricata Linn., Psidium guajava Linn., Lagerstroemia speciosa (L.) Pers., Hibiscus esculentis Linn., Amomum zingiber Linn., Myrtus cumini Linn., Garcinia mangostana Linn., and Aloe vera Linn. Decoction process is used to prepare the leaves of the medicinal plants for medical consumption in the form of tea. Conclusion: This study confirms the use of different plant species to treat diabetes. It further affirms that most people with diabetes in the study areas rely on traditional medicine for their primary health care needs.